COVID-19 infection among nursing personnel: a retrospective survey in Kolkata, West Bengal - Adhikari, Uma Rani; Gupta, Shampa; Bhattacharjee, Soumi (International Journal Of Community Medicine And Public Health, 2022)
Background: During this COVID-19 pandemic the health care workers are at greatest risk of exposure and subsequently developing SARS-CoV-2 infection. Multiple factors determine the severity of illness and its prognosis. This study aims to assess the incidence and severity of COVID-19 infection among the nursing personnel in Kolkata, West Bengal and determines the factors in severity of COVID-19 infection in the reported positive case. Methods: A cross sectional survey was carried out among 858 nursing personnel in Kolkata, West Bengal from April 2021 to March 2022. Demographic and clinical data were collected through semi structured questionnaire and they were tested for validity and reliability before data collection. Results: Result showed that 12.9% nursing personnel are COVID-19 affected. 66.7% belonged to the age group 18-25 years, 100% female and 73% were single. Out of 111 COVID-19 affected, 36.9% were fully vaccinated and 8.1% were partially vaccinated before COVID-19 infection, 16.2% were having comorbidity. Exposure source was not known for 74.8% and from the 25.2% known exposure cases 53.6% developed symptoms in <1 week. 45.9% suffered 2-3 weeks and 33.3% were having some post COVID-19 health problem. Data revealed that severity of illness was significantly associated with comorbidity (X2=5.820) and vaccination status (X2=7.058). Post COVID-19 health problem was significantly associated with age (X2=12.586), comorbidity (X2=12.538) and vaccination status (X2=17.838). Conclusions: Occurrence and severity of COVID-19 infection is less in vaccinated cases. Age, comorbidity and vaccination are the important factors in severity and developing post COVID-19 health problem.